SCN10A-knock-out improves survival and proarrhythmia in a transgenic heart failure mouse model. (25th November 2020) - Bengel, P.R.F; Krekeler, C; Ahmad, S; Hartmann, N; Tirilomis, P; Maurer, W; Toischer, K; Maier, L.S; Hasenfuss, G; Streckfuss-Boemeke, K; Dybkova, N; Sossalla, S
Abstract: Background: In heart failure (HF) both Ca2+/Calmodulin-dependent protein-kinase II (CaMKII) and late sodium current (INaL) are known to contribute to arrhythmogenesis as they contribute to action-potential (AP) prolongation and the occurrence of early- (EADs) and delayed afterdepolarizations (DADs). Further, augmented CaMKII and INaL maintain a vicious cycle as they both can activate each other. We recently found that the sodium channel isoform NaV1.8 is upregulated in HF and hypertrophy and that it is involved in INaL-generation. In the current study we investigated the effects of NaV1.8-knock-out (KO) on HF-progression and arrhythmogenesis in a CaMKII-overexpressing HF mouse model. Methods/Results: CaMKII overexpressing mice (CaMKII+/T) were crossbred with NaV1.8-KO mice (SCN10A−/−). To our surprise knock-out of NaV1.8 in CaMKII+/T mice (SCN10A−/−/CaMKII+/T) significantly improved survival (median survival 103 days vs 74.5 CaMKII+/T, p<0.01). CaMKII+/T mice exhibited a strong HF phenotype compared to WT with increased heart-weight to tibia length ratio as well as reduced ejection fraction and left-ventricular end-diastolic diameter obtained by echocardiography. However, these structural parameters did not differ between SCN10A−/−/CaMKII+/T and CaMKII+/T. Therefore, cellular electrophysiology experiments were performed in isolated cardiomyocytes for a better understanding of the observed improvement in survival. INaL, measured by patch-clamp technique, was significantly augmented in CaMKII+/T vs WT and SCN10A−/−, while SCN10A−/−/CaMKII+/T showed significantly less INaL than CaMKII+/T alone. Further, AP-duration (APD) was significantly reduced in SCN10A−/−/CaMKII+/T vs CaMKII+/T while AP-amplitude, resting membrane-potential and upstroke velocity (dv/dtmax) remained unchanged. In addition, the occurrence of afterdepolarizations was significantly lower in SCN10A−/−/ CaMKII+/T vs CaMKII+/T. Confocal microscopy using the dye Fluo-4AM was performed and significantly less diastolic Ca2+-waves occurred in SCN10A−/−/CaMKII+/T compared to CaMKII+/T. In order to analyze an organ-specific SCN10A-KO, we generated homozygous SCN10A-KO lines of induced pluripotent stem cells by using CRISPR/Cas9 technology. 2-month old iPSC-cardiomyocytes lacking NaV1.8 were treated with low dose isoprenaline and showed significantly less INaL, thereby serving as a final proof of the relevant role of this Na+-channel on INaL-generation in the cardiomyocyte. Conclusion: We found a survival benefit by selective knock-out of the neuronal sodium channel isoform NaV1.8 in a proarrhythmic HF mouse model with augmented CaMKII expression. However, in our model NaV1.8-knock-out showed no effects on HF progression, while cellular proarrhythmic triggers were attenuated. Taken together with our findings in IPS-cardiomyocytes treated with the CRSIPR/Cas9 technology NaV1.8 plays a significant role for the generation of INaL and cellular arrhythmogenic triggers in the cardiomyocyte. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Deutsche Stiftung für Herzforschung